Making Sense of Natural Disasters - Abdul Kabir Hussain Solihu (International Institute of Islamic Thought, 2007)
Islam states that both natural phenomena and humanity are created in the best conceivable pattern. Yet the physical world experiences occasional disasters that threaten sustainable development. This study seeks to provide a framework for understanding this phenomenon within the Islamic ethico-religious perspective by focusing on such natural disasters as earthquakes, cyclones, subsidence, and floods. In an attempt to demonstrate this, I highlight the Qur’anic perspective of how natural resources have been overwhelmingly a source of boon and occasionally a source of bane. Drawing on that perspective, I provide two accounts for a proper understanding of this phenomenon: a macroscopic perspective that dissociates disastrous effects from natural disturbances, and another perspective that, based on moral law, attributes disasters to humanity’s violation of the divine moral law. That is, natural disasters are not disastrous to all creations unless they befall vulnerable communities, and when they are disastrous they are not natural but human-induced. Both perspectives suggest the imperative of the ecosystem and the divine moral law in the course of social and natural development.